Integrating Academic Talent, Personal Resilience, and Study Persistence: The Role of DAT in University Counseling Services - Rofiqah Rofiqah; Abd. Hamid Cholili; Muhammad Arif Furqon (STAI Hubbulwathan Duri, 2025)
Balancing academic talent with personal and academic resilience is essential for sustaining students’ commitment to their studies. Counseling programs aim to reinforce personal resilience and enhance persistence among students. This study explores the individual and combined effects of academic talent and personal resilience on study persistence. It also evaluates student responses to three academic support initiatives: the Differential Aptitude Test (DAT), Academic Guidance and Counseling (BKA), and Advanced Educational Guidance and Counseling (BEKAL). A quantitative research design was employed with 233 student participants. Academic talent was assessed using the DAT, personal resilience via the Resilience Scale for Adolescents (READ), and study persistence through the Persistence/Voluntary Dropout Decisions Scale. Multiple regression analysis was used to examine the relationships between these variables. Findings revealed statistically significant positive correlations between academic talent and personal resilience, academic talent and study persistence, and personal resilience and study persistence (all p = 0.000). Academic talent and personal resilience together accounted for 57% of the variance in study persistence. Additionally, students expressed favorable views of the DAT, BKA, and BEKAL programs, citing their value in guiding academic major selection. The results underscore the importance of integrating academic and personal development strategies in educational planning. Counseling interventions like DAT, BKA, and BEKAL can play a critical role in fostering resilience and improving student persistence.